Isolated left ventricular non-compaction: clinical characterisation of a teenage male - Javeria Khan; Hina Sohail; Parveen Akhtar; Abdul Qadir Memon; Bisma Jalil (Journal of the Pakistan Medical Association, 2024)
Isolated Left Ventricular Non-compaction (LVNC) is a type of cardiomyopathy that usually has a genetic origin. Its diagnosis is based on findings such as deep intertrabecular recesses or sinusoids and ventricular trabeculations communicating with the left ventricular cavity. LVNC was first clinically recognised almost four decades back, yet its diagnostic and management challenges persist. In this report, we present the case of an 18-year-old boy, who presented at the National Institute of Cardiovascular Diseases, Karachi, in March 2023, with complaints of dizziness, pedal oedema, and shortness of breath. Echocardiography revealed signs suggestive of LVNC, which were confirmed conclusively on Cardiovascular Magnetic Resonance (CMR) (NC/C ratio>2.4). The patient underwent implantable cardioverter defibrillator (ICD) placement, was discharged after a smooth post-procedure recovery, and is doing well on follow-ups. ---Continue